Pathogenesis of myonecrosis induced by crude venom and a myotoxin of Bothrops asper. - Ownby, Charlotte L. (1984)
The pathogenesis of skeletal muscle necrosis induced by crude Bothrops asper venom and isolated myotoxic phospholipase was studied using light and electron microscopy. White mice were injected intramuscularly with a dose of 2.5 micrograms/g and tissue samples were taken at 30 min and 1, 3, 6, 12, 24, and 48 hr. Toxin-injected muscle showed localized wedge-shaped lesions ("delta lesions") by 30 min, which included disrupted plasma membranes. At 1 and 3 hr the predominant type of necrotic cell contained clumped myofibrils in which individual myofilaments were indistinguishable. At later time periods there was a relaxation and redistribution of myofilaments resulting in a more homogeneous and hyaline appearance of necrotic cells. Some mitochondria were swollen and had flocculent densities, and most of them were disrupted, having only one membrane and vesiculated cristae. The basal lamina was intact at all time intervals. Phagocytosis of muscle cell debris started at 3 hr and was prominent by 24-48 hr. In crude venom-injected muscle many cells showed pathologic features identical to those observed after myotoxin injection. Crude venom also induced hemorrhage which was evident 30 min after injection, reaching its highest level by 12 hr. At 3, 6, and 12 hr some cells were undergoing different pathologic changes which appeared to be due to ischemia. Although these cells were irreversibly damaged, as indicated by ruptured plasma membrane, their myofibrillar structure was better preserved than that of toxin-affected cells. The Z line was absent, but A, I, H, and M bands were intact. As a result of Z line loss, sarcomeres were disoriented. It is proposed that the myotoxin induces myonecrosis by first altering the integrity of the plasma membrane, thereby increasing the permeability to calcium, other ions, and molecules which leads to death of the cell. Crude venom affects muscle cells in two ways: by direct action of myotoxin (s) and by ischemia due to hemorrhage.